2017
DOI: 10.1049/iet-bmt.2016.0112
|View full text |Cite
|
Sign up to set email alerts
|

System for multimodal biometric recognition based on finger knuckle and finger vein using feature‐level fusion and k‐support vector machine classifier

Abstract: In this study, the authors propose a multimodal biometric system by combining the finger knuckle and finger vein images at feature-level fusion using fractional firefly (FFF) optimisation. Biometric characteristics, like finger knuckle and finger vein are unique and secure. Initially, the features are extracted from the finger knuckle and finger vein images using repeated line tracking method. Then, a newly developed method of feature-level fusion using FFF optimisation is used. This method is utilised to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…In multimodal biometric recognition system, repeated line tracking technique was also implemented to obtain feature extraction. In Reference [65], the repeated line tracking approach with feature-level fusion using fractional firefly (FFF) optimization was employed to extract features from finger knuckle and finger vein images.…”
Section: Vein-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In multimodal biometric recognition system, repeated line tracking technique was also implemented to obtain feature extraction. In Reference [65], the repeated line tracking approach with feature-level fusion using fractional firefly (FFF) optimization was employed to extract features from finger knuckle and finger vein images.…”
Section: Vein-based Methodsmentioning
confidence: 99%
“…Conventional finger vein identification approach uses the distance-based matching technique, while by machine learning techniques finger vein recognition can employ classifier-based matching technique. Classifier-based matching techniques were employed by References [29,49,61,65,85,86,99,100] for finger vein recognition systems. Table 3 summarizes the conventional finger vein recognition approaches, and Table 4 shows the machine learning algorithms-based FVR methods.…”
Section: Matchingmentioning
confidence: 99%
“…Veluchamy et al [1] proposed a multimodal biometric system based on the fusion of finger knuckle and finger vein features by making use of novel technique fractional firefly (FFF) optimization method. To extract the features from finger knuckle and finger vein images line tracking method is adopted.…”
Section: Related Workmentioning
confidence: 99%
“…Recent survey as shown that in today's real world most of the Biometric systems are unimodal systems which depends on one source of information for authentication [1]. Some of the widely known biometrics adopted for human identifications are single fingerprint, iris, face, voice, and DNApalmprint and hand vein.…”
Section: Introductionmentioning
confidence: 99%
“…32 Some works combine the fusion of fingerprints-face features, 33,34 others fused face and iris biometrics. 35 Other interesting approaches are the fusion of finger knuckle and finger vein, 36 and many other combinations.…”
mentioning
confidence: 99%